Gas phase ion formation from a liquid beam of arginine in aqueous solution by IR multiphoton excitation - Kohno, J.; Toyama, N.; Buntine, Mark; Mafuné, F.; Kondow, T. (Elsevier, 2006)
A liquid beam of aqueous solutions of arginine (AH), its hydrochloric acid salt (AH2Cl) and its sodium salt (ANa) was irradiated with a pulsed IR laser at 3509 cm−1 (2.85 μm). Positive and negative ions ejected to the gas phase were mass analyzed. From the AH2Cl and the ANa aqueous solutions, the pre-existing ions in the solution were ejected directly to the gas phase. From the AH solution, on the other hand, both a protonated arginine ion, AH2+ and an argininate ion, A− were observed in the gas phase. Production of these ions is accounted for the four-photon excitation of water molecules in the solution.